Factors in Stunting Prevention with Family Planning: Literature Review - Dini Indo Virawati; Ega Ersya Urnia; Cristinawati B/R Haloho (PT Bukuloka Literasi Bangsa, 2025)
The prevalence of stunting in Indonesia among children aged 0-23 months was approximately 32.9% in 2013. In 2016, the value decreased to 26.1% but increased in 2018 to 29.9%. The results of a nutrition study in Indonesia (SSGI) in 2021 show that the prevalence of stunting in toddlers is approximately 24.4%. In East Kalimantan, the prevalence of stunting is approximately 22.8%, which is lower than the national prevalence. From the previous study, the prevalence of stunting increases in large families with more than 3 toddlers, mothers who visit health care less than 4 times during pregnancy, baby boys, children aged 12-23 months, and babies with low birth weight (<2500 g). One way to control the causes is by using contraception. This research used a literature review of three articles selected based on inclusion characteristics, namely articles published within the last 4 years, with an ISSN, and using a cross-sectional method. The results from the 3 articles indicate that there is a relationship between contraception and a decrease in stunting, and we suggest empowering contraception users to prevent stunting. Keywords: contraception, stunting.